2014
DOI: 10.1002/adfm.201401842
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Study of the N‐Type Doping Efficiency in Solution‐processed Fullerenes and Fullerene Derivatives

Abstract: Molecular doping of organic semiconductors and devices represents an enabling technology for a range of emerging optoelectronic applications. Although p‐type doping has been demonstrated in a number of organic semiconductors, efficient n‐type doping has proven to be particularly challenging. Here, n‐type doping of solution‐processed C60, C70, [60]PCBM, [70]PCBM and indene‐C60 bis‐adduct by 1H‐benzimidazole (N‐DMBI) is reported. The doping efficiency for each system is assessed using field‐effect measurements p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
86
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 74 publications
(92 citation statements)
references
References 40 publications
4
86
0
Order By: Relevance
“…Evidently, the here investigated fullerene mixtures feature excellent charge transport properties, which are on par with results reported for solution-processed pristine fullerenes. [5,18] It is worth noting that the absence of ordered domains (see Supporting…”
Section: / 18mentioning
confidence: 99%
See 2 more Smart Citations
“…Evidently, the here investigated fullerene mixtures feature excellent charge transport properties, which are on par with results reported for solution-processed pristine fullerenes. [5,18] It is worth noting that the absence of ordered domains (see Supporting…”
Section: / 18mentioning
confidence: 99%
“…Despite their desirable solid-state properties a major disadvantage of pristine C60 and C70 is the seemingly poor solubility in organic solvents, [1,2] which however can be substantially improved by attaching exohedral moieties to the fullerene cage, albeit at the expense of a high electron mobility. [3][4][5] In addition, pristine fullerenes suffer from the strong tendency to crystallize during solvent removal, which complicates formation of continuous thin films. As a result, substituted fullerenes, such as in particular phenyl-Cx-butyric acid methyl esters (PCBMs; x = 61 or 71), are by far the most widely studied electron acceptor material for organic photovoltaic applications.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…27 Comparative studies of the doping efficiency of fullerene-based OSCs with the same dopant in OTFTs also found a significant enhancement in device performance. 28 However, conjugated polymers, as the major class of solution-processable OSCs, are rarely n-doped in devices, especially OTFTs, 14,20,24,29 despite the significant improvement it can have on device parameters, e.g., charge carrier mobility, threshold voltage, channel current on/off ratio and contact resistance. Amongst the candidate conjugated n-type polymers for OTFTs, naphthalenediimide (NDI) containing copolymers have shown impressive performance to date.…”
Section: Introductionmentioning
confidence: 99%
“…To this end, recent work has shown that -under certain circumstances -doping organic semiconductors can indeed yield OTFTs and integrated circuits with improved operating characteristics. [31] [32] To assess the impact of doping, different molecular dopants were investigated with the most promising being the fluorinated fullerene derivative C60F48 [ Figure 2(a)]. [33] [34] [35] The attractive properties associated with C60F48…”
mentioning
confidence: 99%